Coronavirus Infection in Neonates: Neurodevelopmental Outcomes at 18 Months of Age - Mariam Ayed; Zainab Alsaffar; Zainab Bahzad; Yasmeen Buhamad; Ali Abdulkareem; Alaa AlQattan; Alia Embaireeg; Mais Kartam; Hessa Alkandari (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Although most neonates with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection experience only mild disease, its impact on neurodevelopmental outcomes is unknown. This study aimed to assess the 18-month neurodevelopmental outcomes of infants who had SARS-CoV-2 infection as neonates. Methods. The authors conducted a prospective cohort study of neonates diagnosed with SARS-CoV-2 infection from June 2020 to December 2020 through nasopharyngeal coronavirus disease 2019 (COVID-19). A total of 58 neonates were identified from the Kuwait National COVID-19 Registry and enrolled. Historical controls were selected from the neonatal follow-up registry and matched in a 2 : 1 ratio based on sex and gestational age. When the subjects were 18 months of age, their neurodevelopmental outcomes were assessed by two trained assessors using the Bayley Scales of Infant and Toddler Development-3rd Edition (BSID-III). Results. Forty children diagnosed with SARS-CoV-2 infection were included in the final analysis. The median age at infection was 18 days (range: 10–26 days). Eighteen (45%) patients were asymptomatic, 15 (37.5%) had a sepsis-like presentation, 5 (12.5%) exhibited respiratory distress, and 2 (5%) had a multisystem inflammatory syndrome in children (MIS-C)-like presentation. At the 18 months follow-up, only one child showed a severe developmental delay and one child had a language delay. BSID-III outcomes did not differ significantly between the SARS-CoV-2-infected and control groups. Conclusions There was no difference in neurodevelopmental outcomes at 18 months in children infected with SARS-CoV-2 compared with controls, although longer neurodevelopmental follow-up studies are required.